Outer dark - McCarthy, Cormac 1933-2023 (Vintage Internat., 1993)
This stark novel is set in an unspecified place in Appalachia, sometime around the turn of the century. A woman bears her brother's child, a boy; he leaves the baby in the woods and tells her he died of natural causes. Discovering her brother's lie, she sets forth alone to find her son. Both brother and sister wander separately through a countryside being scourged by three terrifying and elusive strangers, headlong toward an eerie, apocalyptic resolution.